Clinical and virological characteristics of calves experimentally infected with a Brazilian isolate of bovine viral diarrhea virus type 1a - Luana Marchi Quadros (Ciência Rural)
ABSTRACT: To study the pathogenicity of the Brazilian bovine viral diarrhea virus (BVDV) type 1a 241.10 isolate, four calves were intranasally inoculated with a viral suspension containing 107.2 TCID50 mL-1. One calf was left uninoculated and kept in contact with the other calves to investigate viral transmissibility. After inoculation, the animals were monitored daily for clinical signs of infection. The presence of the virus in the blood and nasal secretions was confirmed by virus isolation in cell culture. White blood cells were quantified prior to and every 3 days after infection, and the presence of antibodies was checked every 7 days, starting at day 0 until day 42 post-inoculation (pi). After infection, nasal and ocular serous secretions were observed between days 1 and 5 pi, along with a mild cough from days 2 to 4 pi; however, no severe clinical signs were present. Body temperature was slightly elevated between days 4 and 6 pi. The control calf did not develop any of the signs observed in the infected animals. Cell culture-mediated virus isolation confirmed viremia between days 4 and 8 pi and the presence of the virus in the nasal secretions between days 1 and 10 pi. All infected animals showed a decrease in white blood cell count. Antibodies could be detected from day 14 pi, and these levels remained high until day 35 pi. The control calf had no viremia, viral presence in nasal secretions, or positive serology, indicating the absence of viral transmission. Thus, isolate BVDV 1a 241.10 has low pathogenicity and transmissibility but retains immunosuppressive capacity.